Tujuan Pelaksanaan Yoga dalam Kitab Bhagawadgita - Negara, Gede Agus Jaya (Institut Hindu Dharma Negeri Denpasar, 2021)
Deity's holy teachings contained in the holy books of religion are a guide for everyone so as not to get lost on the journey of life to achieve the expected goals. Every person who lives in this world has the same goal, namely to want a comfortable, calm, full of joy and happiness, and to be kept away from worldly suffering. One of the many holy books of Hinduism that we can use as a guide to achieving the goal of Hinduism, namely the union between Atma and Paramatma (moksa) is the Bhagawadgita book, which contains the essence of Vedic teachings conveyed by conversation activities between Arjuna and Sri Krisna. One of the discussions in the conversation was about the implementation of yoga as a step-by-step guide to mankind to be able to control themselves to achieve a prosperous life in the world and spiritual happiness called moksa, union with Brahman.